Factors and Solutions for Decreasing Interest in Learning the Al-Qur'an among Post-Primary School Children in Pasar Senen Village, Kerinci - Sari, Atin Anggela; Alfian, Muhammad; Rasmita (UIN Sulthan Thaha Saifuddin Jambi, Pusat Kajian Kurikulum Pengembangan Pengajaran dan Pembelajaran (Center of Curriculum Studies, Teaching and Learning Development), 2024)
The Qur'an contains complete and perfect teachings and laws which cover all aspects needed in human life, especially Muslims. The Al-Quran is the foundation for all knowledge because the Al-Quran explains aqeedah and strengthens a Muslim's faith. A child who studies and understands the Qur'an is expected to have noble morals and be filial to his parents. It is a shame that interest in reading, especially reading the Quran, among some aged children decreases after elementary school. Generally, children stop learning the Quran at TPA after they finish elementary school. They actually spend their time after coming home playing games, the internet, watching, without proper time control so that children are more engrossed in playing with their electronic devices than learning to read the Quran. This research is a type of qualitative research, which is classified as case research. The data obtained came from correspondents, namely children and teenagers as well as parents from the Pasar Senen Village community. This research data was collected using observation and interview techniques. Based on the research results, it is known that the decline in interest in learning the Al-QurÃ¡n for children after graduating from elementary school in Pasar Senen Village, Kerinci Regency is caused by several factors, namely: (a) children's factors (laziness, pride, the burden of schoolwork, feeling they can do it) (b) environmental factors (television programs or other electronic media, parental factors and learning factors. As a follow-up to these problems, parents and recitation teachers should provide motivation and instill awareness from an early age in children, that learning the Quran is an obligation that must be carried out by Muslims which is useful for the world and the hereafter. It is necessary to control and manage time for children.